Legal Aspects of Consumer Protection in E-Commerce Transactions: Implementation and Urgency of Regulations in the Digitalization Era - Sella Ellissa Devita Sari; Mutiara Wikant Saphira; Theodore Sibarani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Digitalization is an activation of the use of digital-based technology. This process is certainly influenced by increasingly sophisticated technological developments. Currently, digitalization continues to develop and expands to all areas of human life, such as education, industry, electronic transactions, electronic media and other fields. Digitalization is here to provide efficiency, effectiveness, provide convenience, and shorten time for individual and group performance. Electronic transactions are transactions carried out between sellers and buyers in contractual relationships using an electronic system. Electronic transactions can be used by anyone, anytime and anywhere. People as consumers get convenience, speed, ease of payment systems, time efficiency when carrying out electronic transactions using E-commerce or other media. On the other hand, electronic transactions still have shortcomings. Lack of use of electronic transactions such as the enactment of standard contracts, legal terms of agreement in drafting contracts have not been implemented effectively, electronic system and transaction operators have not provided legal protection for consumers if losses arise, termination of access to consumers, identity changes by sellers, fraud, and many more . Therefore, Consumer Legal Protection is very important in carrying out electronic transactions. The state can play a role in providing legal protection for consumers through preventive, repressive efforts, as well as with legislation for the interests of weak parties.